DAMPAK PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA KELAS 4 DI SD PEMBANGUNAN LABORATORIUM UNP - Tiara Salsabila; Martin Kustati; Gusmirawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning motivation of fourth-grade students who often appear unfocused and hesitant to participate in classroom activities, therefore the study aims to examine how the use of rewards can influence their learning drive, and it employs a descriptive qualitative approach through observations and interviews so that students’ learning behaviors can be explored in an authentic manner, and the findings reveal that rewards help foster feelings of joy, increase students’ confidence in expressing their ideas, encourage healthy academic competition, and enhance active participation during learning, thus noticeable improvements in learning behavior emerge when rewards are applied consistently, and the study concludes that rewards have a positive impact on learning motivation when given appropriately, proportionally, and according to students’ needs, and the study further suggests that educators should be more creative in selecting reward forms that not only stimulate temporary motivation but also strengthen intrinsic motivation, while combining them with varied teaching methods to maintain an engaging classroom atmosphere and to support the optimal achievement of learning objectives.